Spinal cord injury secondary to electrocution in a dog. (23rd January 2015) - Ros, C.; de la Fuente, C.; Pumarola, M.; Añor, S.
<x xml:space="preserve">Abstract</x> A 13‐year‐old, female spayed, crossbreed dog of 32 kg was presented for evaluation of peracute onset of non‐ambulatory tetraparesis after chewing an electrical wire. Neurological examination was consistent with a C1‐C5 myelopathy. Magnetic resonance imaging revealed a focal intramedullary lesion over the C2‐C3 vertebral bodies, which was confirmed to be an acute focal necrotising poliomyelopathy with subarachnoid and subdural haemorrhages on postmortem examination. This report describes the clinical, imaging and histopathological findings of this unusual type of spinal cord injury, and the effects of electrocution in the central nervous system of dogs.